b n appalling story /c - Bulgakov, Mikhail (b, 2007)
"Sharik is a hapless stray dog, baffled observer of human kind and vitriolic hater of cats. He is plucked from the streets of communist Moscow by Preobrazhensky, a medical professor, and subjected to a bizarre, human-gland-transplanting experiment. When Sharik begins to transform in weird and unexpected ways, his creator's virtuoso scientific confidence turns rapidly to wonderment, and then to horrified soul-searching. Bulgakov's hilarious science fiction is an angry satire of the utopian communist dream gone spectacularly awry, in which sinister forces lurk everywhere. Written in 1925 but immediately banned by the early Soviet government, the novella captures, in a unique style that alternates lucid realism with drama, the atmosphere of its rapidly changing times." "Andrew Bromfield's new translation is accompanied by an introduction by James Meek, which places the work in the context of the Russian class struggles of the era and considers the vision, progressive style and lasting relevance of an author who was isolated and suppressed in his own lifetime. This edition also contains notes and a chronology
Keywords: Animal experimentation -- Fiction. -- Soviet Union; Animal experimentation